Treatment outcome of patients with chondroblastic osteosarcoma of the limbs and pelvis. (June 2019) - Tsagozis, P.; Laitinen, M. K.; Stevenson, J. D.; Jeys, L. M.; Abudu, A.; Parry, M. C.
Abstract : Aims: The aim of this study was to identify factors that determine outcomes of treatment for patients with chondroblastic osteosarcomas (COS) of the limbs and pelvis. Patients and Methods: The authors carried out a retrospective review of prospectively collected data from 256 patients diagnosed between 1979 and 2015. Of the 256 patients diagnosed with COS of the pelvis and the limbs, 147 patients (57%) were male and 109 patients (43%) were female. The mean age at presentation was 20 years (0 to 90). Results: In all, 82% of the patients had a poor response to chemotherapy, which was associated with the presence of a predominantly chondroblastic component (more than 50% of tumour volume). The incidence of local recurrence was 15%. Synchronous or metachronous metastasis was diagnosed in 60% of patients. Overall survival was 51% and 42% after five and ten years, respectively. Limb localization and wide surgical margins were associated with a lower risk of local recurrence after multivariable analysis, while the response to chemotherapy was not. Local recurrence, advanced patient age, pelvic tumours, and large volume negatively influenced survival. Resection of pulmonary metastases was associated with a survival benefit in the limited number of patients in whom this was undertaken. Conclusion: COS demonstrates a poor response to chemotherapy and a high incidence of metastases. Wide resection is associated with improved local control and overall survival, while excision of pulmonary metastases is associated with improved survival in selected patients. Cite this article: Bone Joint J 2019;101-B:739–744.